Four-Step Route to Novel Bisflavylium Dications – First Synthesis of Phloroglucinol-Type Derivatives - Kueny-Stotz, Marie; Brouillard, Raymond; Chassaing, Stefan (Synlett, 2012)
Various bisflavylium dications have been prepared in an efficient four-step manner utilizing the acid-mediated condensation between bis(arylethynylketones) and activated phenols as the key step. Of special note is that phloroglucinol-type bisflavylium salts have been obtained for the first time thanks to this procedure.
Keywords: chromophores; condensation; flavylium; phenols; polycations